PlasmidHawk improves lab of origin prediction of engineered plasmids using sequence alignment - Qi Wang (Nature Portfolio, 2021)
Advances in synthetic biology and genome engineering raise awareness of potential misuse. Here, the authors present PlasmidHawk, a sequence alignment based method for lab-of-origin prediction.